Comparison of sensory structures on the antenna of different species of Philopotamidae (Insecta: Trichoptera). Issue 1 (January 2018) - Melnitsky, Stanislav I.; Ivanov, Vladimir D.; Valuyskiy, Mikhail Yu; Zueva, Lydia V.; Zhukovskaya, Marianna I.
Abstract: Structure and distribution of sensilla were studied in sixteen species of the caddisfly family Philopotamidae. Their antennae bear numerous curved trichoid and pseudoplacoid sensilla and fewer coronal, styloconic and chaetoid sensilla on the flagellar segments. The most numerous pseudoplacoid sensilla have non-specific localization. The curved trichoid sensilla form clusters ventrally on each antennal segment. Sensilla belonging to coronal, styloconic and chaetoid types have specific positions. Long grooved trichoid sensilla are located nonspecifically in all the studied species. The average number of sensilla per segment decreases from the proximal to distal part of the flagellum. Scapus and pedicellum are devoid of most types of sensilla, however, they bear the Böhm bristles and long trichoid sensilla. A positive correlation between antenna dimensions and its cuticular structures is found. Highlights: Seven types of sensilla were found in Philopotamidae arranged in 2 tiers. There are 2 patterns of sensilla distribution, specific and non-specific. Average sensilla numbers per segment decreases from base to apex of flagellum. Subfamily Chimarrinae have less sensilla numbers than Philopotaminae, their sensilla are smaller.